A new species of Cryptonympha Lugo-Ortiz & McCafferty (Ephemeroptera, Baetidae) from Cerro Duida (Venezuela) - Derka, Tomáš; Nieto, Carolina (Zootaxa, 2018)
The genus Cryptonympha includes three species: C. copiosa Lugo-Ortiz & McCafferty, 1998; C. dasilvai Salles & Francischetti, 2004 and C. genevievae Thomas, Manchon & Glémet, 2013, known only from the nymphal stage. A description of the nymph of a fourth representative, Cryptonympha tracheata sp. n. is provided here, based on material collected in a blackwater stream on the slopes of the Cerro Duida mountain in south-western Venezuela. The nymph of the new species can be easily distinguished from the other species of the genus by very long tracheal gills II–VII, 2.5 times the length of each tergum, gill I small, nearly half length of gill IV and by posterior margin of terga with rounded spines. A complete description of the new species and a key for nymphs of all known Cryptonympha species are provided.